2018
DOI: 10.1038/s41422-018-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of the reciprocally inhibitory loop between the ubiquitin-specific protease USP43 and EGFR/PI3K/AKT drives breast carcinogenesis

Abstract: Hyperactivation of EGFR/PI3K/AKT is a prominent feature of various human cancers. Thus, understanding how this molecular cascade is balanced is of great importance. We report here that the ubiquitin-specific protease USP43 is physically associated with the chromatin remodeling NuRD complex and catalyzes H2BK120 deubiquitination. Functionally this coordinates the NuRD complex to repress a cohort of genes, including EGFR, which are critically involved in cell proliferation and carcinogenesis. We show that USP43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 56 publications
1
44
2
Order By: Relevance
“…For Western blotting, membranes were incubated with appropriate antibodies for 1 hour at room temperature or overnight at 4°C followed by incubation with a secondary antibody. Immunoreactive bands were visualized using a Western blotting Luminol reagent (Santa Cruz Biotechnology) according to the manufacturer's recommendation (40).…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…For Western blotting, membranes were incubated with appropriate antibodies for 1 hour at room temperature or overnight at 4°C followed by incubation with a secondary antibody. Immunoreactive bands were visualized using a Western blotting Luminol reagent (Santa Cruz Biotechnology) according to the manufacturer's recommendation (40).…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway can be considered as a master regulator for cancer, 43 as it plays a vital role in BC translation, proliferation, growth, apoptosis, and cell differentiation. 44,45 Moreover, studies have shown that activated PPAR was involved in tumor promotion, cell differentiation, and apoptosis. By analyzing these biological processes and signaling pathways, we found that target genes may play a key role in the progression of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that EGFR leads to receptor tyrosine kinase autophosphorylation and further activated downstream intracellular signaling cascades especially the phosphatidylinositol 3kinase-AKT serine/threonine kinase 1 (PI3K-AKT) pathway, by binding with its cognate ligands [67,68].…”
Section: Lpp-as2 Decoys Mir-7-5p To Upregulate the Expression Of Egfrmentioning
confidence: 99%